Relationships between lignin content and fermentability of intact and chemically treated big bluestem fiber - Cochran, R.C.; Towne, G.; Titgemeyer, Evan C.; Olson, K. C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
An accurate assessment of forage quality is required to allow prediction of animal performance. One of the most commonly used methods of forage evaluation is to measure lignin content, with more heavily lignified materials being considered less digestible. Two measures of lignin, acid detergent lignin (ADL) and acetyl bromide lignin (ABL), were assessed with regard to their ability to predict forage digestibility. Big bluestem forage samples were collected from three ungrazed, annually burned pastures at 38, 58, and 97 days postburn. These times were selected to represent a broad range of forage quality. Cell wall material was treated chemically by: 1) partial delignification (chlorite), 2) isolation o f "- cellulose, or 3) NaOH extraction. Control and treated cell-w all material was analyzed for ABL and ADL and 24 and 72 hr in vitro dry matter disappearance (IVDMD). ABL increased with advancing maturity for intact fibers, whereas ADL was highest in the most mature forage but lowest for the intermediate maturity. Fermentability of the intact fiber decreased with maturity and was correlated highly to ABL content. ABL was a better indicator of forage degradability for intact bluestem fiber than was ADL, but neither ABL nor ADL was adequate for evaluating fermentability of treated residues.
Keywords: Beef; Big bluestem; Forage quality; Lignin